RzeczPiSpolita POlska. Geografia wyborcza Platformy Obywatelskiej oraz Prawa i Sprawiedliwości w latach 2005-2010 - Skobrtal, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The competition between Civic Platform (PO) and Law and Justice (PiS) in recent 5 years has led to the reflection about the territorial aspect of these divisions. Particulary interesting is the distribution of votes. A few tendentions like presence of historical divisions can be observed. The aim of this paper is to analyse these divisions and the main factors of their occurance.